AdipoRon Promotes the Osseointegration of Dental Implants in Mice With Type 2 Diabetes Mellitus - Huang, BoRui; Bi, Wei; Sun, Yang; Li, Ruixue; Wu, Xingwen; Yu, Youcheng (Frontiers in Physiology, 2021)
To explore the effect of AdipoRon on bone absorption and bone integration of Type 2 diabetes (T2DM) mice with implants, we established surgery-induced model of osseointegration of dental implantation in T2DM mice of C57BL/6 db/db and normal mice homologous to diabetic mice. Micro CT was used to analyze the femurs with the plant in the mice to detect the bone mass, HE, TRAP, and safranin O- fast green staining was performed to analyze the bone formation and bone resorption. Bone integration related markers as Rankl, BMP2, OPG, OPN, and Runx2 were also measured using immunohistochemistry. Our results indicated that diabetic mice showed a lower bone mass, decreased osteoblast differentiation. AdipoRon attenuated diabetes-induced BV/TV, Tb.Th, Tb.N, and Tb.Sp as well as bone integration related markers variation and promoted bone hyperplasia as well as represses osteoclast formation especially in diabetic mice. AdipoRon may improve the osseointegration of dental implants in mice with type 2 diabetes through promoting osteogenesis and inhibiting bone resorption and AdipoRon may serve as a promising oral strategy to improve the osseointegration ability of diabetic patients.